2007
DOI: 10.1021/tx7000509
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxidation oftrans-4-Hydroxy-2-Nonenal Is Aldehyde Dehydrogenase Isozyme and Mg2+Dependent

Abstract: trans-4-Hydroxy-2-nonenal (HNE) is a cytotoxic alpha,beta-unsaturated aldehyde implicated in the pathology of multiple diseases involving oxidative damage. Oxidation of HNE by aldehyde dehydrogenases (ALDHs) to trans-4-hydroxy-2-nonenoic acid (HNEA) is a major route of metabolism in many organisms. HNE exists as two enantiomers, (R)-HNE and (S)-HNE, and in intact rat brain mitochondria, (R)-HNE is enantioselectively oxidized to HNEA. In this work, we further elucidated the basis of the enantioselective oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The 3D BALDH model and substrate-docking modeling of the BALDH active site with benzaldehyde and phenylacetaldehyde were obtained based on the crystal structure of the human mitochondrial ALDH2 (Protein Data Bank code 1CW3B) as described previously (Brichac et al, 2007).…”
Section: Modeling and Substrate Docking For Baldhmentioning
confidence: 99%
“…The 3D BALDH model and substrate-docking modeling of the BALDH active site with benzaldehyde and phenylacetaldehyde were obtained based on the crystal structure of the human mitochondrial ALDH2 (Protein Data Bank code 1CW3B) as described previously (Brichac et al, 2007).…”
Section: Modeling and Substrate Docking For Baldhmentioning
confidence: 99%
“…In addition, ALDH2 also contributes to detoxification of the dopamine metabolite 3,4-dihydroxyphenylacetaldehyde. It has been shown that during this detoxification process, the enzyme encoded by this gene can catalyze the transformation of toxic acetaldehyde products to acetic acid (Meyer et al, 2004;Brichac et al, 2007;Leiphon and Picklo, 2007). Meyer et al (2004) and Vermeer et al (2012) reported that trans-4-hydroxy-2-nonenal and 3,4-dihydroxyphenylacetaldehyde are associated with disease of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…acetaldehyde to acetic acid. The major lipid peroxidation products 4-hydroxy-2-nonenal (4HNE) and malondialdehyde (MDA) are also detoxified by ALDH2 [23,24]. ALDH2 has the highest affinity for acetaldehyde, an important intermediary product of ethanol metabolism.…”
Section: Aldh2mentioning
confidence: 99%
“…This is because individuals lacking ALDH2 will likely be exposed to higher levels of endogenous aldehydes from birth, such as 4HNE and MDA [23,24], thereby requiring an alternate defence system. In fact, Aldh2 knockout mice had higher levels of heme oxidase 1, an essential defensive factor against cellular oxidative stress, without any pre-treatment [54].…”
Section: Mechanism Of Liver Damage Amelioration Induced By Congenitalmentioning
confidence: 99%